2014
DOI: 10.1371/journal.pone.0101577
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Drivers of Flexibility in Summit Metabolic Rates of Small Birds

Abstract: Flexible metabolic phenotypes allow animals to adjust physiology to better fit ecological or environmental demands, thereby influencing fitness. Summit metabolic rate (Msum = maximal thermogenic capacity) is one such flexible trait. Skeletal muscle and heart masses and myocyte metabolic intensity are potential drivers of Msum flexibility in birds. We examined correlations of skeletal muscle and heart masses and pectoralis muscle citrate synthase (CS) activity (an indicator of cellular metabolic intensity) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
4
20
0
Order By: Relevance
“…However, migratory (Driedzic et al, 1993) and seasonal (Dawson and Marsh, 1989;Swanson, 2010) stability in pectoralis CS activities are also common in birds. The increases in mass-specific pectoralis CS activities for both training protocols in this study, along with the significant positive correlations between pectoralis CS activities and organismal metabolic capacities, are consistent with other house sparrow data, as total pectoralis CS activity increases in winter relative to summer (Liknes and Swanson, 2011) and pectoralis CS activity is positively correlated with M sum (Swanson et al, 2014a). Collectively, these studies suggest that increases in pectoralis CS activities are important to increased organismal capacities for exercise and shivering in house sparrows.…”
Section: Cellular Lipid Catabolic Capacity and Metabolic Intensitysupporting
confidence: 90%
See 2 more Smart Citations
“…However, migratory (Driedzic et al, 1993) and seasonal (Dawson and Marsh, 1989;Swanson, 2010) stability in pectoralis CS activities are also common in birds. The increases in mass-specific pectoralis CS activities for both training protocols in this study, along with the significant positive correlations between pectoralis CS activities and organismal metabolic capacities, are consistent with other house sparrow data, as total pectoralis CS activity increases in winter relative to summer (Liknes and Swanson, 2011) and pectoralis CS activity is positively correlated with M sum (Swanson et al, 2014a). Collectively, these studies suggest that increases in pectoralis CS activities are important to increased organismal capacities for exercise and shivering in house sparrows.…”
Section: Cellular Lipid Catabolic Capacity and Metabolic Intensitysupporting
confidence: 90%
“…Positive correlations of pectoralis CS activity with both M sum and MMR for sparrows in the present study suggest that cellular metabolic intensity contributes to training effects for house sparrow. This is not necessarily the case for birds generally, as previous studies showed that M sum was also positively correlated with pectoralis CS activity in house sparrows, but not for other birds Swanson et al, 2014a). In addition, MMR was only significantly positively correlated with pectoralis CS activities in male red junglefowl (Gallus gallus), but not in female red junglefowl or house sparrows (Hammond et al, 2000;Buttemer et al, 2010).…”
Section: Correlationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Given the absence of regional differences in maximum thermogenic capacity (Ribeiro, Prats, et al, ), the wider metabolic expansibility observed in populations experiencing lower winter temperatures (Central and Inland populations; mean minimum temperature in winter <2°C) inescapably stems from the lower BMR. Thus, as opposed to northern‐temperate climates, where highly variable climates select for higher maximum thermogenic capacity (Swanson, Zhang, & King, ), subtropical and highly variable climates should select for lower BMR.…”
Section: Discussionmentioning
confidence: 99%
“…While shivering thermogenesis results from cellular processes, namely the activation of 44 energetic metabolism pathways to burn cellular fuels to power skeletal muscle contraction 45 (Hothola 2004), it can be quantified at the organism-level as the maximum thermoregulatory 46 metabolic capacity (M sum ; (Thompson 2010)). In fact, several studies showed that cold 47 temperatures lead to increases in M sum (Vezina et al 2011) (Swanson et al 2014a). One 48 explanation for this flexibility in maximum metabolic capacity is the cold adaptation hypothesis, 49 which posits that birds wintering in cold climates should have higher M sum than those in warmer 50 climates, and hence high M sum is critical for overwinter survival in very cold regions (Marsh and 51 pectoralis muscle which is the primary thermogenic organ (Vézina et al 2006) (Swanson et al 59 2014a); iii) increase in enzymatic activity in oxidative metabolic pathways (Vézina et al 2006) 60 (Zheng et al 2014) (Liknes and Swanson 2011a); and iv) increase in fat catabolism (Dawson et 61 al.…”
mentioning
confidence: 99%